Equity Pairs Trading on the JSE Using Single Stock Futures - Paine, Sean James (My University, 2014)
This research report investigates the key factors which contribute to the risks and potential profits of pairs trading. It then expounds on the relationship between these key factors and the success of pairs trading. Although previous research has investigated the success of pairs trading in general, this research delves into how pairs trading may be “fine-tuned” to produce the greatest risk-adjusted returns. It is also the first known study of this nature on the JSE. The problem identified by the research is to define and analyse a hedge fund trading strategy based on the concept of pairs trading using cointegration. This includes determining the key independent variable parameters that are then used to define the pairs trading strategy, and then testing which values are optimal for the key independent variable parameters. Data were collected from a secondary source, a commercial provider of daily stock market data. This was the only source of data for the research. The data were then run through an application which simulated trades based on certain quantifiable conditions. This software was written by the researcher. The key findings of the research are that there are two key independent variables which can be used to influence the success of pairs trading. These variables are the cointegration t-statistic, a measure of how cointegrated a pair of shares are, and the opening trading signal variable. The key message of the research is that by adjusting the two identified variables to suit the risk profile of a fund, it is possible to produce meaningful returns from pairs trading.
MBA thesis
Keywords: Johannesburg Securities Exchange; Pairs trading